Polymer-Antimicrobial Peptide Constructs with Tailored Drug-Release Behavior - Pola, Robert; Vícha, Matěj; Trousil, Jiří; Grosmanová, Eliška; Pechar, Michal; Rumlerová, Anna; Studenovský, Martin; Kučerová, Emilie; Ulbrich, Pavel; Vokatá, Barbora; Etrych, Tomáš (Pharmaceutics, 2023)
Microbial resistance is one of the main problems of modern medicine. Recently, antimicrobial peptides have been recognized as a novel approach to overcome the microbial resistance issue, nevertheless, their low stability, toxicity, and potential immunogenic response in biological systems have limited their clinical application. Herein, we present the design, synthesis, and preliminary biological evaluation of polymer-antibacterial peptide constructs. The antimicrobial GKWMKLLKKILK-NH2 oligopeptide (PEP) derived from halictine, honey bee venom, was bound to a polymer carrier via various biodegradable spacers employing the pH-sensitive or enzymatically-driven release and reactivation of the PEP's antimicrobial activity. The antibacterial properties of the polymer-PEP constructs were assessed by a determination of the minimum inhibitory concentrations, followed by fluorescence and transmission electron microscopy. The PEP exerted antibacterial activity against both, gram-positive and negative bacteria, via disruption of the bacterial cell wall mechanism. Importantly, PEP partly retained its antibacterial efficacy against Staphylococcus epidermidis, Escherichia coli, and Acinetobacter baumanii even though it was bound to the polymer carrier. Indeed, to observe antibacterial activity similar to the free PEP, the peptide has to be released from the polymer carrier in response to a pH decrease. Enzymatically-driven release and reactivation of the PEP antimicrobial activity were recognized as less effective when compared to the pH-sensitive release of PEP.
Keywords: drug delivery; HPMA copolymers; bacteria; antimicrobial peptides